Bioactive peptides with the inhibitory activity that are produced by lactic acid bacteria; their importance and mechanism (Texas Journal of Agriculture and Biological Sciences, 2022)
The inhibitory action of peptides refers to a group of microorganisms that peptides can influence and inhibit. Most peptides have limited inhibitory action, as their effect is limited to bacteria which close to the bacteria that produce them, especially lactic acid peptides. As most of them are characterized by a broad inhibitory action extending to include unrelated bacteria from Gram-positive bacteria and pathogenic or food spoilage bacteria, and in some cases, they include lactose-negative bacteria too. The main application of lactic acid bacteria is to use it as priorities, as it contributes to strengthening the flavor, feeling, and nutritional value of the different fermentation through three main paths, which are the fermentation of sugars, fats analysis, and the main path to manufacture and develop the flavor which is the protein analysis. In order to develop new functional foods that provide a beneficial health effect, many tests are carried out for lactic acid bacteria strains. To be used in food production, taking into consideration the economic feasibility, required sensory characteristics, and consumer acceptance. In addition, testing it on the living body to know its effect on the digestive system using analytical methods. Bioactive peptides are considered valuable nutritional components that have biological properties and many therapeutic effects for many health disorders, especially heart diseases and cancer, in addition to many chronic diseases. And because it has a functional factor that has beneficial effects on the health of the consumer, it has been studied extensively, as it can be absorbed in the intestine without digestion, it is preferable to be used over free amino acids, as it is transmitted at the same level as the transport of free amino acids by the cell. Moreover, free amino acids make foods hyperactive and may cause diarrhea, while some bioactive peptides may cause allergic reactions, as the allergenic effects disappear with partial weight reduction. However, the use of peptides remains a matter of great importance in food preservation in terms of providing food safety, ensuring the quality of the food supply, and prolonging the shelf life